Structural performance of stainless steel reinforced concrete members: A review. (28th March 2022) - Rabi, Musab; Shamass, Rabee; Cashell, K.A.
Highlights: The paper presents a thorough review of the existing knowledge on stainless steel reinforced concrete structural member including the material behaviour and existing performance data. Stainless steel reinforcement is typically used for applications where its corrosion resistance and long life cycle is desirable although it is becoming increasingly desirable owing to current sustainability targets. Further suggestions for future research are highlighted. Abstract: Degradation of reinforced concrete (RC) infrastructure because of corrosion of the steel reinforcement is a well-known and expensive global problem. The inspection, repair, maintenance and replacement costs are a huge drain on resources, while the consequent disruption damages productivity. Existing measures to improve the performance of failing RC structures are generally retrospective and do not aid the sustainability agenda, nor do they effectively reduce the maintenance requirements over the remaining design life of the structure. In light of this, the replacement of traditional, corrodible, carbon steel reinforcement with inherently corrosion-resistant stainless steel reinforcement in the design of concrete structures and infrastructure is a viable and attractive solution. There has been a rapid increase in interest in this topic in recent years from the engineering research community, mainly owing to the growing problem of aging and deteriorating infrastructure as well as the lack of available and appropriate performance data and design guidance for stainless steel reinforced concrete. This paper presents a state-of-the-art review of stainless steel reinforced concrete, both at a material and structural level and assembles and thoroughly reviews the known information as well as identifying the key gaps. The paper is aimed at both the research community, to drive future research agendas, as well as practicing engineers so they can employ sustainable and maintenance-free stainless steel reinforced concrete more readily and with confidence.